please do this............very urgent AP one
Attachments:
![](https://hi-static.z-dn.net/files/dbf/4a8b20855f61aff30964efdd84a002e6.jpg)
Answers
Answered by
4
In an A.P., the common difference is constant
So, 2k + 1 - k + 3 = 4k + 3 - 2k - 1
=> k + 4 = 2k + 2
=> k - 2k = 2 - 4
=> -k = -2
=> k = 2
Hope this helps......
So, 2k + 1 - k + 3 = 4k + 3 - 2k - 1
=> k + 4 = 2k + 2
=> k - 2k = 2 - 4
=> -k = -2
=> k = 2
Hope this helps......
Answered by
0
Given 1st term T1 = (k - 3).
Given 2nd term = (2k + 1).
Given 3rd term = (4k + 3).
Given that they are in AP.
T2 - T1 = T3 - T2
(2k + 1) - (k - 3) = (4k + 3) - (2k + 1)
2k + 1 - k + 3 = 4k + 3 - 2k - 1
k + 4 = 2k + 2
4 = 2k + 2 - k
4 = k + 2
4 - 2 = k
k = 2.
Therefore the value of k = 2.
Hop this helps!
Given 2nd term = (2k + 1).
Given 3rd term = (4k + 3).
Given that they are in AP.
T2 - T1 = T3 - T2
(2k + 1) - (k - 3) = (4k + 3) - (2k + 1)
2k + 1 - k + 3 = 4k + 3 - 2k - 1
k + 4 = 2k + 2
4 = 2k + 2 - k
4 = k + 2
4 - 2 = k
k = 2.
Therefore the value of k = 2.
Hop this helps!
siddhartharao77:
:-))
Similar questions